Bone Manifestations of Neurofibromatosis Type 1 - Ibrahima Dokal Diallo; Zaynab Iraqi Houssaini; Mehdi Tantaoui; Wend-Yam Mohamed Traoré; Behyamet Onka; Siham El Haddad; Latifa Chat; Nazik Allali (SAGE Publishing, 2022)
Von Recklinghausen disease is the most common phacomatosis. It can affect many systems, including the bone system. Through these 2 cases, we illustrate the bone manifestations of this disease.